Clinical Study of the Relation between Mucosal Healing and Long-Term Outcomes in Ulcerative Colitis - Kaoru Yokoyama; Kiyonori Kobayashi; Miyuki Mukae; Miwa Sada; Wasaburo Koizumi (Gastroenterology Research and Practice)
Background and Objectives. Mucosal healing (MH) is considered an important therapeutic goal in ulcerative colitis (UC). We evaluate the severity of intestinal inflammation and clarify the relation between MH and long-term outcomes. Methods. The study group comprised 38 patients with UC in clinical remission on total colonoscopy who were followed up for at least 5 years. Clinical remission was defined as a Mayo score of 0 for both stool frequency and rectal bleeding. Colonoscopic findings were evaluated into 4 grades according to the Mayo endoscopic subscore (MES). Results. During clinical remission, the MES was 0 in only 24% of the patients, 1 in 40%, 2 in 26%, and 3 in 10%. Seventy-six percent of the patients thus had active disease on colonoscopy. After initial colonoscopy, the cumulative rate of remission maintenance was 100% in MES 0, 1 in 93%, 2 in 70%, and 3 in 50% at 6 months and 78%, 40%, 10%, and 0%, respectively, at 5 years (). Conclusion. Many patients with UC in clinical remission have active lesions. Patients with a higher MES have a higher rate of recurrence. To improve long-term outcomes, an MES of 0 should be the treatment goal.